Oral versus intravenous maternal hydration in isolated third trimester oligohydramnios - Zafar, Humaira; Naz, Mubashra; Fatima, Umber; Shahzad, Uzma; Fatima, Anees; Yasmeen, Attiya (International Journal of Research in Medical Sciences, 2020)
Background: To study the effect of oral and intravenous maternal hydration in patients with isolated oligohydramnios in terms of mean change in amniotic fluid. Methods: A total number of 38 patients included in the study which fulfill the selection criteria. Patients were randomly divided in two groups. Amniotic fluid index (AFI) of all patients was measured before the hydration therapy according to the method of Phelan et al. In maternal oral hydration (Group A), every patient was instructed to drink two liters of water over two hours daily for 1 week. In intravenous hydration (Group B), every woman infused two liters of 0.9% normal saline in two hour daily for 1 week. After 48 hours and 1 week of oral and intravenous hydration, the AFI was reassessed by the same observer. Patients were monitored closely for sign and symptoms of fluid overload. Data was stratified for mean difference in improvement in amniotic fluid index. Results: After oral hydration therapy AFI was 5.926±0.4593 after 48 hours and 8.286±0.6000 after 7 days in Group A. In Group B AFI was 5.784±0.4622 after 48 hours and 7.868±0.2810 after 7 days of intravenous hydration. P value after 48 hours is 0.348 and p=0.014 after 7 days means oral hydration therapy significantly increase amniotic fluid index. Conclusions: Oral maternal hydration significantly increase the amniotic fluid index in patients with isolated oligohydramnios. It is simple, safe and non-invasive method.